The cGAS/STING–TBK1–IRF Regulatory Axis Orchestrates a Primitive Interferon-Like Antiviral Mechanism in Oyster - Qiao, Xue; Zong, Yanan; Liu, Zhaoqun; Wu, Zhaojun; Li, Yuanmei; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2021)
Interferon (IFN) system is considered as the first defence line against viral infection, and it has been extensively studied in vertebrates from fish to mammals. In invertebrates, Vagos from arthropod and IFN-like protein (CgIFNLP) from Crassostrea gigas appeared to function as IFN-like antiviral cytokines. In the present study, the CgIFNLP protein in haemocytes was observed to increase after Poly (I:C) stimulation. After CgIFNLP was knocked down by RNAi, the mRNA expression of IFN-stimulated genes (CgISGs) was significantly inhibited. Both cyclic GMP-AMP synthase (CgcGAS) and stimulator of interferon gene (CgSTING) identified from oyster were able to recognize the double-stranded nucleic acid (Poly (I:C) and dsDNA) and expressed at high level after Poly (I:C) stimulation. The expression of CgIFNLP and interferon regulatory factors (CgIRF1/8) as well as the nuclear translocation of CgIRF8 were all suppressed in CgcGAS-RNAi or CgSTING-RNAi oysters after Poly (I:C) stimulation. The expression level of CgSTING and TANK binding kinase1 (CgTBK1) did not decrease in CgcGAS-RNAi oysters. After CgSTING was knocked down, the high expression of CgTBK1 induced by Poly (I:C) was prevented significantly. These results indicated that there was a primitive IFN-like antiviral mechanism dependent on the cGAS/STING-TBK1-IRFs regulatory axis in molluscs, which was different from the classic cGAS-STING-TBK1 signal pathway in mammals.